Individual knowledge management engagement, knowledge-worker productivity, and innovation performance in knowledge-based organizations: the implications for knowledge processes and knowledge-based systems - Butt, M. A. (2019)
The literature on the knowledge management relatively ignores an important concept, the individual knowledge management engagement-the degree to which a knowledge worker is involved with the knowledge management-related activities. This concept is imperative for nurturing the productivity of knowledge workers, knowledge management architecture effectiveness, and innovation. Therefore, this study proposes the mediating role of knowledge-worker productivity between individual knowledge management engagement and innovation. The data were collected from the 330 knowledge workers of IT sector of Pakistan and analyzed using the SmartPLS 3 Version 2.6. The results indicate the partial mediation of knowledge-worker productivity between the individual knowledge management engagement and innovation. The results suggest the pivotal role of individual knowledge management engagement in increasing the innovation and knowledge-worker productivity in the knowledge-based organizations.